FORMATION OF LEGAL COMPETENCE OF FUTURE ENGINEERS-PEDAGOGUES IN THE PROCESS OF VOCATIONAL TRAINING - Kotelevets , O.; Kravchenko, Н. (Problems of Engineer-Pedagogical Education, 2023)
Legal competence is an integral part of the vocational training of future engineers-pedagogues and a component of legal competence of a specialist. The article examines the process of forming legal competence of future engineers-pedagogues in the conditions of a higher education institution. Attention is drawn to the levels of formation of legal competence of a person: the level of formation of key legal competencies, the level of formation of basic legal competencies, and the level of formation of special legal competencies. In the process of forming legal competence in future engineers-pedagogues, a significant role is played by the educational component, which involves the development of theoretical, practical and personal components of legal competence. It is noted that the educational and professional bachelor's degree program in higher education institutions covers a wide range of modern innovative vectors of development of the theory and practice of modern vocational education in general and vocational (vocational and technical) education in particular, but does not pay attention to the formation of legal competence. One of the ways to improve the educational process of legal training of future engineers-pedagogues is the active use of modern pedagogical technologies. Interactive teaching technologies contribute to the formation of self-determination (the ability to develop one's own position in life); the acquisition of an individual worldview; the ability to set and fulfill tasks; and also contribute to self-realization and assertion of oneself as a personality in legal matters. At the same time, a special place is occupied by training technologies and the project method. Trainings in the field of legal relations, human resources management, legal conflict resolution, communication training, decisionmaking training, etc. become effective for students during their training. The use of the project method contributes to the implementation of certain pedagogical tasks faced by teachers (intensification of the educational process, improvement of its efficiency and quality of student learning outcomes; systematic integration of subject tasks, etc.), and also contributes to the manifestation of student's abilities to solve legal problems of a wider range of research and to establish legal relations between students.